METAFICTION AND REPRESENTATION OF GENDERED IDENTITY IN GILLIAN FLYNN'S "GONE GIRL" - Soheila Farhani Nejad (English Studies at NBU, 2025)
This study examines the interplay of gender stereotypes in crime narratives through the lens of Gillian Flynn's Gone Girl. Flynn's novel challenges traditional portrayals of women in crime fiction, positioning them not merely as victims but as complex anti-heroines capable of orchestrating elaborate criminal plots fueled by vengeance and psychological manipulation. The paper highlights the metafictional elements in Gone Girl, where the author employs self-conscious storytelling to critique societal expectations surrounding gender roles. By intertwining themes of media representation, domesticity, and the neoliberal notion of choice, the paper underscores how Flynn's narrative structure critiques the commodification of female identity and the performative aspects of gender roles and identity. Ultimately, the study posits that Flynn's work serves as a thought-provoking commentary on the power dynamics inherent in the representation of gender in contemporary media culture, revealing the complexities of identity as shaped by societal constructs.